2019
DOI: 10.1182/blood-2018-09-872028
|View full text |Cite
|
Sign up to set email alerts
|

Randall-type monoclonal immunoglobulin deposition disease: novel insights from a nationwide cohort study

Abstract: Monoclonal immunoglobulin deposition disease (MIDD) is a rare complication of B-cell clonal disorders, defined by Congo red negative–deposits of monoclonal light chain (LCDD), heavy chain (HCDD), or both (LHCDD). MIDD is a systemic disorder with prominent renal involvement, but little attention has been paid to the description of extrarenal manifestations. Moreover, mechanisms of pathogenic immunoglobulin deposition and factors associated with renal and patient survival are ill defined. We retrospectively stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
92
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 42 publications
6
92
4
Order By: Relevance
“…We did not observe a direct correlation between renal and haematological responses as described in other studies . Some patients showed haematological responses but not RR.…”
Section: Discussioncontrasting
confidence: 82%
“…We did not observe a direct correlation between renal and haematological responses as described in other studies . Some patients showed haematological responses but not RR.…”
Section: Discussioncontrasting
confidence: 82%
“…Our model also enabled us to analyse the intrinsic toxicity of pathogenic monoclonal LC for plasma cells. Similarly to what was shown in patients with MIDD (52,23,5,10) and in the HCDD model (17), plasma cells producing LCDD LC are highly sensitive to PI. We assume that mouse plasma cells are quite different from dysplasic human plasma cells, in that genomic alterations other than the sole LC production could explain such sensitivity.…”
Section: Discussionsupporting
confidence: 62%
“…This could be due to the higher level of circulating MIg in PGNMID-LC than PGNMID-IgG and/or may also reflect differences in the mechanisms of complement activation and glomerular inflammation induced by the deposition of monoclonal LCs. (iv) In more than two-thirds of PGNMID-IgG patients, no monoclonal gammopathy or bone marrow B-cell clone are detected at diagnosis or on follow up, 2,7,18,26 and it has been suggested that an oligoclonal response with the same IgG light-and heavy-chain isotype could be involved in the development of glomerulonephritis, at least in some cases. 7 Thus, only 9%-32% PGNMID-IgG patients have a detectable nephropathic clone.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2 patients with molecular studies, pIs of the complete V domains and of the CDRs were low, contrasting with cationic values found in LCDD LCs that may play a role in their interaction with anionic basement membranes in LCDD. 2 However, additional molecular analyses of LCs from patients with PGNMID-LC are needed to characterize the overall pattern of LCs in this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation